2008
DOI: 10.1136/bjsm.2007.040212
|View full text |Cite
|
Sign up to set email alerts
|

Increased mast cell numbers in human patellar tendinosis: correlation with symptom duration and vascular hyperplasia

Abstract: Objectives: The cellular basis of painful tendon overuse pathology (tendinosis) is poorly understood. It has been suggested that because of the close anatomical associations between mast cells and vessels in connective tissues, mast cells may mediate the development of tendon hypervascularity or oedema. Objectives: To examine the distribution of mast cells in men and women with patellar tendinopathy. Design: Case-control study. Methods: Tendinopathic tissue was collected at open debridement of the patellar ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
66
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 38 publications
8
66
1
1
Order By: Relevance
“…This increase of MCs was particularly prominent in the MTJ but was also seen in the mid-tendon and BTJ. Previous clinical studies based on samples derived from patients suffering from AT rupture have provided limited support for an increase in MC numbers during healing (Scott et al 2008). Moreover, an increase in MC density has been suggested after rabbit deep flexor tendon repair (Berglund et al 2010) and in the tendinopathy seen in the calcaneal tendon overuse rat model (Pingel et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This increase of MCs was particularly prominent in the MTJ but was also seen in the mid-tendon and BTJ. Previous clinical studies based on samples derived from patients suffering from AT rupture have provided limited support for an increase in MC numbers during healing (Scott et al 2008). Moreover, an increase in MC density has been suggested after rabbit deep flexor tendon repair (Berglund et al 2010) and in the tendinopathy seen in the calcaneal tendon overuse rat model (Pingel et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…7 This study contributes evidence that tendon repair is physiologically influenced by mast cells and their products which are known to accumulate following injury. 6 Mast cells may be involved in the initial inflammation following injury, and may also influence later events through the secretion or release of soluble factors, Figure 3. Patellar tendons were systematically examined with multiphoton (A,D,G) and second harmonic generation (B,E,H) and merged images were created (C,F,I)-all images at same magnification (63Â objective, please see Materials and Methods Section for details).…”
Section: Discussionmentioning
confidence: 99%
“…6 Mast cells, in addition to their well known role in mediating allergic reactions, also contribute to the repair and remodeling phases of soft tissue healing by releasing factors which promote proliferative and fibrogenic activity (e.g., TGFb, PDGF) as well as potent enzymes known to influence tissue repair in a variety of ways (e.g., mast cell tryptase, CPA3). A previous study reported an increased number of mast cells following acute tendon injury, 7 but to our knowledge there has not been an experimental approach to examine the implications of mast cell inhibition following tendon injury.…”
mentioning
confidence: 99%
“…When specific immunolabeling is performed, mast cells are found to be more prominent in tendinopathy tissue, mostly in association with microvessels (57). These mast cells express tryptase, a potent angiogenic factor (57). Mast cells are also a prominent source of nerve growth factor, which may play a role in the neural sprouting described above for acute and chronic tendon injuries (58).…”
Section: Role Of Mast Cells In Tendinopathymentioning
confidence: 99%
“…When specific immunolabeling is performed, mast cells are found to be more prominent in tendinopathy tissue, mostly in association with microvessels (57). These mast cells express tryptase, a potent angiogenic factor (57).…”
Section: Role Of Mast Cells In Tendinopathymentioning
confidence: 99%